2020
DOI: 10.1177/0363546520907106
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Arthroscopic Repair in Patients With Tears of Hypertrophic Versus Morphologically Normal Acetabular Labra

Abstract: Background: Recently, a hypertrophic labrum has been reported in the absence of hip dysplasia, which can possibly contribute to an acetabular labral tear. Purpose: To compare the clinical outcomes and complications, including the incidence of iatrogenic acetabular labrum and cartilage injury, in patients with tears of hypertrophic versus morphologically normal acetabular labra over a minimum follow-up period of 2 years and to assess the morphologic changes at follow-up computed tomography arthrography in the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We measured the width of the labrum at 11:30, 1:30, and 3:00 in MRI scans. Three standardized locations of the anterior to superior labrum were used for the measurements, as described by several studies [ 24 , 25 ]. The length of the labrum was measured at the 11:30 clock-face position on a coronal proton density (PD) sequence, in which we used the posterior border of the indirect head of the rectus femoris tendon as the landmark; at the 3-o’clock position on an axial oblique PD sequence at the psoas U, where the iliopsoas tendon passes anterior to the labrum; and at the 1:30 clock-face position, a half-point between the 11:30 and 3:00 positions on a sagittal fat-suppressed PD image.…”
Section: Methodsmentioning
confidence: 99%
“…We measured the width of the labrum at 11:30, 1:30, and 3:00 in MRI scans. Three standardized locations of the anterior to superior labrum were used for the measurements, as described by several studies [ 24 , 25 ]. The length of the labrum was measured at the 11:30 clock-face position on a coronal proton density (PD) sequence, in which we used the posterior border of the indirect head of the rectus femoris tendon as the landmark; at the 3-o’clock position on an axial oblique PD sequence at the psoas U, where the iliopsoas tendon passes anterior to the labrum; and at the 1:30 clock-face position, a half-point between the 11:30 and 3:00 positions on a sagittal fat-suppressed PD image.…”
Section: Methodsmentioning
confidence: 99%
“…Labral resection/ debridement was originally performed to reduce pain and increase joint function, especially in patients with unstable and/or irreparable labral lesions, and reconstructive techniques have recently become more common [16,17]. Currently, labral repair and reconstruction retain the biomechanical role of the labrum and should allow better chance for hip preservation [3,[18][19][20][21][22]. However, debridement of the unstable peripheral portion of the labrum is technically less demanding and may be associated with a lower rate of intraarticular adhesions [16,23].…”
Section: Introductionmentioning
confidence: 99%
“…Larson relatively definitively has shown that labral repair is better than debridement, 2 so labral debridement in general has appropriately become less used. Some have considered hypertrophic labra to be more prone to failure since it can be associated with hip dysplasia, but in the studies by Brinkman et al 1 and by Lim et al, 3 large labra can still be primarily repaired with good results, assuming that there is not actual bony undercoverage. Primary hip labral reconstruction, as has been recently advocated by White et al, 4 has been shown to yield good outcomes as well.…”
mentioning
confidence: 99%